Spatiotemporal Dynamics of the Harpan River and Its Hydro-ecological Impacts on Phewa Lake, Pokhara, Nepal - Upadhyay, Rajeev; Lamichhane, Debendra Bahadur (The Himalayan Geographers, 2025)
The Harpan River, a principal feeder stream of Phewa Lake in Gandaki Province, Nepal, plays an important role in upholding the hydro-ecological integrity of the lake and river. For many years, the Harpan River system has experienced crucial morphological changes because of many human activities, climate variability, and land use changes. This study provides a spatiotemporal analysis of the course alterations of the Harpan River in recent years 1979, 2014, and 2024 using remote sensing and GIS tools. The river’s morphology has been substantially transformed with the increase of meander, sediment deposition, and channel migration, which have led to severe sedimentation in Phewa Lake. Such transformation has reduced about 24% water storage capacity together with the decline of aquatic biodiversity. The study also emphasizes increasing pollution loads, with the increase of Total Nitrogen (TN) and Total Phosphorous (TP) from agricultural runoff and crude urban waste. Even the tourism and local livelihoods are suffering from the lake’s degradation. This research highlights the necessity of integrated watershed management and conservation planning.